Culturas territoriais no conhecimento e nas práticas do ordenamento do território : um ensaio metodológico - Godinho, Liliana (2013)
The theory and practice of planning have been very adverse to the new conceptions of space. From the approaches of Simin Davoudi e Strange (2009), who sees space as a social product and planning as a social activity, this research seeks the space and territory planning representations. Having the objective of approaching the territorial culture, we seek to assess the influence of the positivist, structuralist and postmodern currents in the ways of conceiving spaces and exercising the practice of planning.